Geographic Information System Proposes Determination Of Business Location Feasibility: Case Study Small Business Culinary In Pontianak - Ristyawan, Mochammad Ridwan (Universitas Muhammadiyah Yogyakarta, 2018)
The growth of Small Medium Enterprises (SME’s) has increased significantly in Pontianak. The new entry of small business resulted high level competition in culinary industry. A small business culinary could be closed to bankruptcy because the determination of business location was not feasible and settle. The customer would be difficult to find the location of the small business because due to non-fixed locations. The owner of small business often ignores the selection of strategic location. Therefore, it is important to establish the appropriate business location feasibility. Geographic Information System (GIS) is an information system that able to visualize the determining factors as a result analyzed spatial data. Analytical Hierarchy Processing (AHP) is a method that used into decision making process with multi criteria and multi alternatives. The spatial data of GIS is used by AHP to determine feasible location of small business. The criteria of spatial data are the number of competitors, infrastructure of location, distance of supplier, rental price of location, population density and traffic density. The spatial data of GIS result the visualization of spreading data in real condition on digital map subsequently be analyzed by AHP method to obtain recommended small business locations. The determination of hierarchy, criteria and priority rating location deliver recommendation the feasibility of culinary small business location.